Prevalence, antimicrobial resistance profile and comparison of selective plating media for the isolation of Salmonella in backyard chickens from Entre Rios, Argentina. (27th October 2017) - Rodríguez, F. I.; Pascal, D. C.; Pulido, D.; Osinalde, J. M.; Caffer, M. I.; Bueno, D. J.
Summary: This study was conducted to estimate the apparent prevalence of Salmonella spp. in birds kept under backyard system in Entre Ríos, Argentina, and determine the performance of two selective plating media used for Salmonella isolation, and the antimicrobial resistance of the isolated. Also, the association of farms characteristics with Salmonella presence was evaluated. A total of 657 backyard chickens and 15 gooses were sampled one time by cloacal swab, belonging to 51 and one family farms, respectively, and four counties in Entre Rios state from April 2014 to May 2015. Only four samples from backyard chickens belonged to three family farms from Uruguay County were positive to Salmonella spp., so the apparent prevalence was 0.6% for this kind of chicken. Four serovars were isolated ( Salmonella ser. Lille, S . ser. Newport, S . ser. Enteritidis and S . ser. Rissen), which were susceptible to all antibiotics tested with the exception of erythromycin. For Hektoen enteric agar and brilliant green agar, relative specificity and positive predictive value were 1, and the relative sensitivity and negative predictive value did not show any difference between them. The agreement was very good between these two plating media. None of the variables studied could be selected to calculate the risk factors associated with Salmonella isolation because p  > .15. Although the prevalence of Salmonella spp. is low in backyard birds in Entre Rios, the presence of S . ser. Enteritidis should not be discounted, because it is found in the county that concentrates a large population of intensive poultry production in the state.